PENGARUH HAN TERHADAP SENTIMEN ANTI-JEPANG DI DALAM INDUSTRI HIBURAN DI KOREA SELATAN PADA TAHUN 2018 – 2020 - Gaizka Hergi Alhabsyi; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Han is a sociocultural concept of Korean society that has a broad definition of the injustice and suffering of Korean society during the colonial period. Han became part of Korean society until recently even after the colonialization of the Empire of Japan had ended. After the normalization of relations between South Korea and Japan, the intense cooperation between the two countries still leaves various identity-related conflicts that disrupt the bilateral relations between the two countries due anti-Japanese sentiments in South Korean society.This study illustrates the distrust of Korean society illustrated through the Haninfluenced South Korean entertainment industry. Jonathan Mercer's Social Identity Theory is used to analyze the relationship between Han's in South Korean society and the anti-Japanese sentiments that exist in the entertainment industry. The phenomena of anti-Japanese sentiment are analyzed using Social Identity Theory obtained through news, journals, books and official statements from the government and related parties. The results showed that han as a community identity influences the collective emotions of Korean society which is reflected in the field of culture and the entertainment industry. The entertainment industry reflects people's views and reactions to Japanese culture that is present in Korean society. The entertainment industry Also played a role in disseminating and producing the concept of han that caused anti-Japanese sentiment. Keywords: Han, Entertainment Industry, Identity, Collective Emotions, Ethnonationalism, Anti-Japanese Sentiment, Social Identity Theory (SIT).